Comparative Capitalisms and Energy Transitions: Renewable Energy in the European Union. (20th January 2020) - Allen, Maria L.; Allen, Matthew M. C.; Cumming, Douglas; Johan, Sofia
Abstract: We develop new theory pertaining to the institutional determinants of renewable energy usage across countries and over time. Building on key strands of the comparative capitalisms literature, we introduce new hypotheses relating to the 2009 Directive from the European Union (EU) on energy generation, as well as the impact of labour market regimes, national stock markets and merger and acquisition (M&A) activity, as well as 'doing business' conditions across countries. Based on renewable energy data from 27 EU countries over a period of 11 years, we provide new tests of the determinants of renewable energy usage. The data show strong and robust evidence of a causal impact of institutional determinants on renewable energy usage, consistent with a positive impact of the EU's 2009 Directive and other specific institutional factors. We discuss the implications for policy and practice.